A new and threatened species of Scinax (Anura: Hylidae) from Queimada Grande Island, southeastern Brazil - Brasileiro, Cinthia A.; Haddad, Celio F. B.; Sawaya, Ricardo J.; Martins, Marcio (Zootaxa, 2007)
We describe a new species of hylid frog, Scinax peixotoi, from Queimada Grande Island, southeastern Brazil. The new species belongs to the Scinax perpusillus species group, in which all known forms inhabit bromeliads, and is diagnosed by the following set of characters: moderate-size (males 18.8–20.7 mm SVL, females 22.4–25.1 mm SVL); canthus rostralis distinct; dorsal skin slightly rugose; and a distinct advertisement call with relatively low dominant frequency. The new species is known from a single population on Queimada Grande, an island of 43 ha, approximately 33 km distant from the coast of São Paulo State, where it inhabits scattered patches of bromeliads. The highly specialized and patchy habitat of S. peixotoi, associated with its small range size, make this species highly susceptible to stochastic or anthropogenic habitat disturbances, which could lead it to extinction.